Impact of vegetable oils on the fatty acid composition of a milk-containing curd product - Belemets, Tatiana; Radzievska, Irina; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana; Pasichnyi, Vasyl; Kochubei-Lytvynenko, Oksana; Frolova, Natalia; Mykoliv, Ivan; Korablova, Olga (My University, 2021)
It was determined that the proposed 50% replacement of the mass fraction of milk fat of milk-containing curd product allows to sufficiently increase the content of monounsaturated and olyunsaturated fatty acids, as well as bring the fatty acid composition of milk-containing product to the theoretical “ideal fat” recommended by nutritionists.
Keywords: blend; milk-containing product; oil; кафедра технології ресторанної і аюрведичної продукції; кафедра технології молока і молочних продуктів; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра технології м’яса і м’ясних продуктів